Comparison of Fracture Resistance Between Two Monolithic and One Veneered Zirconia Materials on Molar Crowns After Thermomechanical Fatigue - KAHRAMANOĞLU, ERKUT (MARMARA UNIV, INST HEALTH SCIENCES, 2020)
Objective: The purpose of this in-vitro study is to evaluate fracture resistance of two monolithic and one veneered zirconia crowns on human molar teeth fabricated after thermomechanical fatigue. Methods: Seventy-two human molar teeth were prepared to receive zirconia crowns. The specimens were divided into three experimental groups (n=24) according to restoration design, monolithic or veneered. The crowns were fabricated from GC initial zirconia, Dentsply Sirona TZI and Dentsply Sirona ZI. The prepared teeth were scanned with Sirona inEos X5 and the restorations were milled using Cerec inLab MC X5. The crowns were cemented by resin cement. Twelve crowns of each experimental group underwent thermomechanical fatigue using chewing Simulator for 240 000 chewing cycles with load of (100 N) and thermocycling (5 degrees C/55 degrees C), the remaining 12 crowns in each group did not undergo any thermomechanical fatigue and were considered as control group. All specimens were loaded until fracture using universal testing machine. Forces were applied to occlusal surface with 90 degrees angle. Loads of fracture were recorded. Collected data of fracture loads of all specimens were analyzed using SPSS 23.00 program. Results: Although thermomechanical fatigue significantly decreased fracture loads of only monolithic groups, monolithic zirconia crowns had higher fracture loads than veneered one. Among all specimens, the highest fracture load was found in GC group (5001,81 N) and the lowest was found in ZI group (2117.37 N). Two fracture patterns were observed among monolithic zirconia groups; total and crack, while three fracture patterns were observed in veneered group; porcelain fracture, porcelain and core, porcelain and core with tooth fracture. Conclusion: Thermomechanical fatigue has significant influence on monolithic zirconia, however, it showed higher fracture loads and can be alternative to veneered design.
Keywords: Zirconia; monolithic; fracture; thermomechanical fatigue; LOAD-BEARING CAPACITY; LITHIUM DISILICATE; DENTAL CERAMICS; HUMAN ENAMEL; 2-BODY WEAR; STRENGTH; BEHAVIOR; DEGRADATION; FAILURE; BRIDGES